Genes in the dopaminergic system and delinquent behaviors across the life course: the role of social controls and risks - Boardman, Jason D. (Criminal justice and behavior, 2014)
This article examines the interaction between social control and social risk mechanisms, and genes within the dopaminergic system (DAT1 and DRD2) as related to serious and violent forms of delinquent behavior among adolescents and young adults. We use nine waves of data from the National Youth Survey Family Study (NYSFS) to examine the relevance of protective or risky social factors at four social levels, including school, neighborhood, friends, and family within the gene?environment interaction framework. We extend previous work in this area by providing a testable typology of gene?environment interactions derived from current theories in this area. We find consistent evidence that the associations between putatively risky genotypes and delinquent behavior are suppressed within protective social environments. We also provide some evidence that supports the differential susceptibility hypothesis for these outcomes. Our findings largely confirm the conclusions of previous work and continue to highlight the critical role of the social environment within candidate gene studies of complex behaviors.